Effect of intergenerational exchange patterns and intergenerational relationship quality on depressive symptoms in the elderly: An empirical study on CHARLS data - Zheng, Ranran; Yu, Mingyang; Huang, Li; Wang, Fang; Gao, Baizhi; Fu, Duanduan; Zhu, Jinghui; Liu, Guilin (Frontiers in Public Health, 2022)
Background: As the population ages with fewer children, depression symptoms are increasing among the elderly who lack companionship. Intergenerational support is closely related to depression in the elderly; hence how the behavioral patterns and emotional quality of intergenerational support affect depressive symptoms in the elderly should be further explored. Objective: To study the effects of intergenerational exchange patterns and intergenerational relationship quality on depressive symptoms in the elderly. Methods: A total of 8,015 people over 60 years old in CHARLS in 2018 were selected as the object of this study. First, the correlation between demographics, economic conditions, health status, intergenerational support patterns, intergenerational relationship quality, and depressive symptoms in the elderly were analyzed. Three regression analysis models were established to analyze the relationship between control variables, intergenerational support patterns, intergenerational relationship quality, and depressive symptoms in the elderly. Results: Among the intergenerational economic, care, and emotional exchange modes, the risk of depressive symptoms in the elderly in the mutual support group was 31.8%, 38.4%, and 25.5% lower than that in the non-communication group. Compared with the elderly with very poor intergenerational relationship quality, the elderly with good, very good, and excellent intergenerational relationship quality had 74.5%, 84.0%, and 85.6% lower risk of depressive symptoms. Discussion: Different cultural backgrounds also affect intergenerational exchange patterns and depression in the elderly. During the study of depressive symptoms, two aspects relating to intergenerational support should be considered behaviorally and emotionally: the intergenerational exchange model and the intergenerational relationship quality. As depression in the elderly is affected by multiple factors, the participation and joint efforts of the whole society are required to reduce depressive symptoms in the elderly and realize active aging. Conclusion: The intergenerational exchange pattern of mutual support and the higher quality of the intergenerational relationship can significantly reduce the depressive symptoms of the elderly.